Synthesis and antiproliferative activity of 1H-1, 2, 3-triazole-4H-chromene-d-glucose hybrid compounds with dual inhibitory activity against EGFR/VEGFR-2 and molecular docking studies. (24th November 2022) - Nguyen, Dinh Thanh; Do, Son Hai; Le, Thi Huyen; Nguyen, Thi Hanh; Nguyen, Minh Huyen; Vu, Thi Ngoc Bich; Pham, Thi Thu Hien; Vu, Ngoc Toan; Hoàng, Thi Kim Van; Nguyen, Thi Kim Giang
Abstract : 1 H -1, 2, 3-Triazole-4 H -chromene-d -glucose hybrids were synthesized and screened for their anticancer activity in vitro against MCF-7, HepG2, HeLa and WI-38 cells, and several had dual inhibitions against EGFR/VEGFR-2. IFD, MM-GBSA and MD simulations were also carried out. Abstract : A series of 1 H -1, 2, 3-triazole-4 H -chromene-d -glucose hybrid compounds 7a-o was synthesized via click chemistry using 2-amino-7-propargyloxy-4 H -chromene-3-carbonitriles 5a-o and peracetylated d -glucopyranosyl azide, respectively. CuNP@montmorillonite K10 was used as the catalyst in the presence of DIPEA. All the synthesized 1 H -1, 2, 3-triazoles exhibited potent anticancer activity in vitro against the tested cancer cells, including MCF-7, HepG2, and HeLa. Almost all these compounds had low cytotoxicity against WI-37 cells. Amongst the tested compounds, some compounds exhibited strong activity against the tested cancer cell lines with IC50 < 5 μM, such as 7g, 7m, and 7o against HepG2, 7b, 7f, 7g, and 7k against MCF-7, 7c, 7e, and 7n against HeLa, and 7b, 7j, and 7n against SK-LU-1 cancer cell lines. Compounds, 7b, 7f, 7g, and 7k, exhibited remarkable dual inhibitory activity against EGFR and VEGFR-2 tyrosine kinases in comparison with erlotinib and sorafenib, respectively. The resulted docking studies showed that the representative compound 7g displayed a similar binding mode to erlotinib in the EGFR enzyme ; 4HJO and showed good binding energies. Induced-fit docking and MM-GBSA calculations were carried out to elucidate the inhibitory potential of compound 7g against the tested enzyme ; 4HJO . The docking analysis showed that between the hydrophilic and hydrophobic interactions at the active site of the EGFR enzyme, the hydrogen-bond binding between the acetate functional group and appropriate amino acid residues displayed the most important contribution in intensifying the potency against this enzyme. The interaction of the Cys773 residue was the decisive interaction for the ligands to reside in the receptor of ; 4HJO, and therefore the activity of the selected inhibitor. Further, 300 ns MD simulation of the 7g /; 4HJO complex showed the stability of the ligand–protein complex and structural insights into its binding mode.